Clinical and Genetic Characteristics of Chinese Children With GLUT1 Deficiency Syndrome: Case Report and Literature Review - Hu, Qingqing; Shen, Yuechi; Su, Tangfeng; Liu, Yan; Xu, Sanqing (Frontiers in Genetics, 2021)
Objective GLUT1 deficiency syndrome (GLUT1-DS) is a rare, treatable neurometabolic disorder. However, its diagnosis may be challenging due to the various and evolving phenotypes. Here, we report the first Chinese familial cases with genetically confirmed GLUT1-DS, and analyze the characteristics of Chinese children with GLUT1-DS from clinical, laboratory and genetic aspects. Methods We reported a Chinese family with three affected members with GLUT1-DS and searched the relevant articles up to September 2020 from PubMed, WOS, CNKI, and WanFang databases. A total of 30 Chinese patients diagnosed with GLUT1-DS (3 newly identified patients in one family and 27 previously reported ones) were included and analyzed in this study. Results The median age of onset of the 30 patients (male: 18, female: 12) was 8.5 months (range, 33 days to 10 years). Epileptic seizures were found in 25 patients, most with generalized tonic-clonic and focal ones. Movement disorders were in 20 patients - frequently with ataxia and dystonia, developmental delay in 25 patients, and microcephaly only in 6 patients. Cerebrospinal fluid (CSF) analysis showed decreased CSF glucose (median 1.63mmol/L, range 1.1 2.6mmol/L) and glucose ratio of CSF to blood (median 0.340, range 0.215 0.484). The genetic testing performed in 28 patients revealed 27 cases with pathogenic variations of the SLC2A1 gene, including 10 missense, 9 frameshift, 3 nonsense, 3 large fragment deletion and 2 splice-site mutations. Most patients had a good response to the treatment of ketogenic diet or regular diet with increased frequency. Although 3 patients in this Chinese family carried the same pathogenic mutation c.73C>T (p.Q25X) in the SLC2A1 gene, their symptoms and responses to treatment were not exactly the same. Conclusions The clinical manifestations of GLUT1-DS are heterogeneous, even among family members sharing the same mutation. For children with unexplained epileptic seizures, developmental delay and complex movement disorders, it is helpful for the diagnosis of GLUT1-DS by detection of low CSF glucose or SLC2A1 gene mutations. Early initiation of ketogenic diet treatment significantly improves the symptoms and prognosis of GLUT1-DS.